An origin of the immunogenicity of in vitro transcribed RNA. Issue 10 (9th March 2018) - Mu, Xin; Greenwald, Emily; Ahmad, Sadeem; Hur, Sun
Abstract: The emergence of RNA-based therapeutics demands robust and economical methods to produce RNA with few byproducts from aberrant activity. While in vitro transcription using the bacteriophage T7 RNA polymerase is one such popular method, its transcripts are known to display an immune-stimulatory activity that is often undesirable and uncontrollable. We here showed that the immune-stimulatory activity of T7 transcript is contributed by its aberrant activity to initiate transcription from a promoter-less DNA end. This activity results in the production of an antisense RNA that is fully complementary to the intended sense RNA product, and consequently a long double-stranded RNA (dsRNA) that can robustly stimulate a cytosolic pattern recognition receptor, MDA5. This promoter-independent transcriptional activity of the T7 RNA polymerase was observed for a wide range of DNA sequences and lengths, but can be suppressed by altering the transcription reaction with modified nucleotides or by reducing the Mg 2+ concentration. The current work thus not only offers a previously unappreciated mechanism by which T7 transcripts stimulate the innate immune system, but also shows that the immune-stimulatory activity can be readily regulated.